1982
DOI: 10.1103/physrevlett.49.1804
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Test of Bell's Inequalities Using Time- Varying Analyzers

Abstract: for trapping as 6 decreases is reflective of the incorporation of periodic components into the sequence of numbers generated.To summarize the motivation and principal conclusion of this Letter, we restate' that for values of b where numerically generated sequences~P Pear to be chaotic, it has not been settled whether those sequences "are truly chaotic, or whether, in fact, they are really periodic, but with exceedingly large periods and very long transients required to settle down. " On the one hand, Grossman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
2,339
1
60

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,363 publications
(2,559 citation statements)
references
References 9 publications
45
2,339
1
60
Order By: Relevance
“…Shocking as it may be, our world is not of this kind. Statistical inequalities, such as e = 1/4, derived on the assumption that the values of unmeasured physical quantities do exist and commonly referred to as Bell's inequalities 33 , have been violated in a number of painstaking experiments 33,34,35,36,37,38,39,40,41,42,43,44 . We shall not dwell on the philosophical implications of this experimental fact (volumes have been written on the subject), but simply point out that it should be embraced by all those who worry about secrecy because what does not exist cannot be eavesdropped, and so it is much easier to keep secrets in a non-classical world.…”
Section: Less Reality More Securitymentioning
confidence: 99%
“…Shocking as it may be, our world is not of this kind. Statistical inequalities, such as e = 1/4, derived on the assumption that the values of unmeasured physical quantities do exist and commonly referred to as Bell's inequalities 33 , have been violated in a number of painstaking experiments 33,34,35,36,37,38,39,40,41,42,43,44 . We shall not dwell on the philosophical implications of this experimental fact (volumes have been written on the subject), but simply point out that it should be embraced by all those who worry about secrecy because what does not exist cannot be eavesdropped, and so it is much easier to keep secrets in a non-classical world.…”
Section: Less Reality More Securitymentioning
confidence: 99%
“…The two other main assumptions include "locality" (10,11) and "freedom of choice" (12). Invoking any of these renders an experiment vulnerable to explanation by a local realistic theory.…”
mentioning
confidence: 99%
“…Thus, the maximal violation of Bell inequality in quantum mechanics has the extra √ 2 factor in the case of a pair of spins [16]. This violation was convincingly tested by Aspect et al [2,3] (see Figure 1) and the quantum entanglement was confirmed as a fundamental aspect of quantum mechanics. 1 To avoid confusion, the tensor product ⊗ is omitted below for simplicity.…”
Section: Bell Inequalitymentioning
confidence: 74%
“…After Aspect et al succeeded in showing experimental evidence of the quantum nature of entanglement by measuring correlations of linear polarizations of pairs of photons [2,3], much attention has been paid to this genuine quantum property in various research areas in quantum information theory.…”
Section: Introductionmentioning
confidence: 99%